2007
DOI: 10.1111/j.1540-5893.2007.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the Lawyer Matter? Influencing Outcomes on the Supreme Court of Canada

Abstract: This article examines the impact of lawyer capability on the decisionmaking of the Supreme Court of Canada (SCC). Extending prior attorney capability studies of U.S. judicial decisionmaking, we test three lawyer variables: prior litigation experience, litigation team size, and Queen's Counsel designation. We find that the first two variables have a statistically significant and positive relationship with the SCC's decisions in non‐reference‐question cases from 1988 to 2000. Moreover, this relationship persists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 32 publications
2
46
0
1
Order By: Relevance
“…Lawyers who appear repeatedly before the same court come to be seen as reliable, knowledgeable, and trustworthy by judges, who then give their arguments greater credence than those proffered by unknown attorneys (Haire, Lindquist, and Hartley 1999;McGuire 1995;Szmer et al 2007). Relational expertise reflects skill at negotiating the interpersonal environments in which professional work takes place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lawyers who appear repeatedly before the same court come to be seen as reliable, knowledgeable, and trustworthy by judges, who then give their arguments greater credence than those proffered by unknown attorneys (Haire, Lindquist, and Hartley 1999;McGuire 1995;Szmer et al 2007). Relational expertise reflects skill at negotiating the interpersonal environments in which professional work takes place.…”
Section: Discussionmentioning
confidence: 99%
“…Substantive professional expertise is abstract and principled, whereas relational expertise is "situated" and "contextual" (Barley 1996:425, 429). The explicit curriculum of professional training-for example, constitutional law, anatomy, homiletics, or fluid dynamics-typically does not include this material; nevertheless, it can be essential for work's successful conduct (Barley 1996; for law specifically, see, e.g., Eisenstein and Jacob 1977;Feeley 1992;Kritzer 1998a;Monsma and Lempert 1992;Sullivan et al 2007;Szmer, Johnson, and Sarver 2007). The explicit curriculum of professional training-for example, constitutional law, anatomy, homiletics, or fluid dynamics-typically does not include this material; nevertheless, it can be essential for work's successful conduct (Barley 1996; for law specifically, see, e.g., Eisenstein and Jacob 1977;Feeley 1992;Kritzer 1998a;Monsma and Lempert 1992;Sullivan et al 2007;Szmer, Johnson, and Sarver 2007).…”
Section: Professional Expertisementioning
confidence: 99%
“…In this respect, we might argue that litigation team size is an important indicator of litigation advantage~see Galanter, 1974!. Indeed, prior studies~see, for example, Szmer et al, 2007! found significant relationships between litigation team size and judicial decisions.…”
Section: Independent Variablesmentioning
confidence: 98%
“…The literature in political science has concentrated on appellate outcomes, which can in most cases be reduced to a binary variable (either the appeal succeeds or it does not), and which has employed indirect measures of lawyer quality (for example: Justice Blackmun's letter grades assigned to counsel at oral argument (Johnson et al, 2006) or experience (Haynie and Sill, 2007) or senior counsel status (Szmer et al, 2007) or past record (Hanretty, 2013)) to test whether better counsel win more appeals. A more general literature in empirical legal studies has focused on continuous outcomes, sometimes monetary outcomes in personal injury cases (Moorhead et al, 1994;Rosenthal, 1974) but more often sentence lengths in criminal trials, where the stakes are particularly high for clients (Abrams and Yoon, 2007;Shinall, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…I collected information on 116 coefficients from 11 different studies (Farole Jr, 1999;Haire et al, 1999;Hanretty, 2013;Haynie, 1994;McGuire, 1995McGuire, , 1998Sheehan et al, 1992;Songer and Sheehan, 1992;Songer et al, 1999Songer et al, , 2000Szmer et al, 2007). The required magnitude on the rank-based measure was greater than 82.8% of coefficients in the cited studies, and greater than greater than 91.4% of coefficients on the list-based measure.…”
mentioning
confidence: 99%